The Impact of Perceived Risk on Consumers’ Cross-Platform Buying Behavior - Zhang, Xiaoxue; Yu, Xiaofeng (Frontiers in Psychology, 2020)
In recent years, social application with shopping have become an indispensable activity in people’s daily life. A number of previous studies have investigated various risks in the online shopping and consumer’s belief. However, few scholars paid more attention to buying behaviour, especially on consumer’s cross-platform buying behaviour. Although consumers can purchase goods directly in platforms that given them information, they also buy target products on other platforms. This study conceptualizes and implements concepts such as perceived risk, trust, negative reports and consumer cross-platform buying behaviour. A questionnaire survey of users (n=366) was conducted, and a basic description and comparison of consumers’ cross-platform buying behaviour was made in terms of consumers’ perception of the risk of product effects, consumers’ perception of service risks and consumers’ perceptions of other risks. The degree of trust in the platform and negative reports about the platform also affect cross-platform buying behaviour. As a result, these findings are discussed and explained, and some reference is provided for related platforms. Besides, the study’s finding concerning consumer’s buying behaviour depends on the security of platform in people’s conceptions.